2019
DOI: 10.1080/01448765.2019.1590234
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution in soils and urban-grown organic vegetables in the province of Sevilla, Spain

Abstract: Heavy metal pollution in urban-grown organic vegetables and soils of the province of Sevilla, Spain Sources of heavy metal pollution in vegetables can be varied. The focus of this study was to determine the factors affecting trace metal pollution in soils and vegetables that are grown on community urban and periurban organic farms in Spain. Results of this study shown that soil and dust deposition affected plant composition more than other anthropogenic sources, such as traffic loads, which showed a small inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…113 The use of brownfields for gardening and wastewater for irrigation can pose serious problems related to contamination of the vegetables produced in these areas. 114,115 Some urban areas studies have shown the levels of pollutant accumulation in vegetables did not threaten human health, such as Barcelona, Spain 113,116 ; Sevilla, Spain 117 ; Lisbon, Portugal 118 ; Madrid, Spain 119 ; Sheffield, UK 120 ; and Braganca, Portugal. 121 However, in other cities, the pollutant levels identified were high and threatened human health, including Rio de Janeiro, Brazil 122 ; Daejeon, South Korea 123 ; Rome, Italy 124 ; Melbourne, Australia 125 ; Dera Ismail Khan, Pakistan 126 ; and Ghaziabad, India.…”
Section: Soil Pollution and Human Healthmentioning
confidence: 99%
“…113 The use of brownfields for gardening and wastewater for irrigation can pose serious problems related to contamination of the vegetables produced in these areas. 114,115 Some urban areas studies have shown the levels of pollutant accumulation in vegetables did not threaten human health, such as Barcelona, Spain 113,116 ; Sevilla, Spain 117 ; Lisbon, Portugal 118 ; Madrid, Spain 119 ; Sheffield, UK 120 ; and Braganca, Portugal. 121 However, in other cities, the pollutant levels identified were high and threatened human health, including Rio de Janeiro, Brazil 122 ; Daejeon, South Korea 123 ; Rome, Italy 124 ; Melbourne, Australia 125 ; Dera Ismail Khan, Pakistan 126 ; and Ghaziabad, India.…”
Section: Soil Pollution and Human Healthmentioning
confidence: 99%
“…Since the late 1970s, there has been an effort to reduce the use of Pb in various products, such as gasoline, paints for residential applications, cans for food products, and plumbing systems [3]. López et al (2019) [27] detected high levels of Pb in the soil of an urban farm, which was attributed to the construction demolition wastes dumped into the soil at the site close to where the urban farm was located. These construction wastes contained white paints, which are characteristic of the Mediterranean countries.…”
Section: Industrial Sourcesmentioning
confidence: 99%
“…This inorganic Cu form is insoluble in water and is, therefore, not washed off easily by irrigation water or rainwater, thereby providing longer protection against diseases [41]. López et al (2019) [27] detected high concentrations of Cu in the leaves of urban plants and linked it to the use of copper-based fungicides, even though traffic pollution is usually considered the main source of Cu released into the environment in urban regions.…”
Section: Agricultural Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the economically developed countries, the risks from consumption of urban vegetable crops are related with emission of pollutants by industrial enterprises and motor vehicles. In particular, the increased concentrations of HM were found in vegetable products of city gardens in Brazil [ 19 ], Korea [ 20 ], Spain [ 21 ], Germany [ 22 ], and many other countries.…”
Section: Introductionmentioning
confidence: 99%